THE INFLUENCE OF SEMANTIC INTEGRATION ON READING PROFICIENCY OF 6TH SEMESTER STUDENTS AT MUHAMMADIYAH TANGERANG UNIVERSITY: A CASE STUDY ON THE NOVEL “THE STRANGE CASE OF DR. JEKYLL AND MR. HYDE” - Aidil Syah Putra; Alvita Farha A; Kukuh Satria (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This study investigates the influence of semantic integration on the reading proficiency of 6th-semester students at Muhammadiyah Tangerang University, focusing on the novel "The Strange Case of Dr. Jekyll and Mr. Hyde." Employing a quantitative research design with pre-test and post-test assessments, the study engaged 10 students majoring in English Literature. Results indicated a significant improvement in reading proficiency, with an average increase of 15 points in test scores. Questionnaire feedback highlighted the effectiveness of semantic techniques in enhancing vocabulary understanding, text comprehension, and critical thinking. Despite limitations such as the small sample size and focus on a single text, the findings underscore the potential of semantic integration strategies to boost academic reading skills. Future research should aim to expand the sample and explore a wider range of literary works to validate and extend these findings